Cherry-plum and its hybrids with male sterility - Є. П. Шоферістов (Plant Varieties Studying and Protection)
The results of first varietal study of 7 new genotypes of Prunus cerasifera Ehrh., bred in Nikitsky Botanical Gardens, with male sterility and one similar introduced variety 'Puntsovy' have been given. The value and defects have been marked. Their practical use in selection work and in nurseries has been suggested.